Emotional Urban Spaces: Atmosphere, Fascination, and Phantasmagoria in Sunetra Gupta’s The Glassblower’s Breath (1993) - Pataki, Éva (Hungarian Journal of English and American Studies, 2021)
Investigating the literary representation of urban spaces and identities the essay untangles the complex psychological and emotional relationship between the heroine and her beloved and hated cities in Sunetra Gupta’s The Glassblower’s Breath (1993). Drawing on Gernot Böhme’s (1993) theory of the atmospheric qualities of space, Steve Pile’s psychogeographical approach to reading cities, Walter Benjamin’s concept of phantasmagoria, and various interpretations of fascination, it explores the creation of atmospheres in the novel and the role of fascination in the perception of London and Gupta’s female protagonist as phantasmagorias. I argue that—as urban imaginaries—the emotional fabric and atmosphere of the cities portrayed are as much created by their spaces and places, their inhabitants and visitors, as they are manifested and formulated in emotional states of being, whether real or fictional, phantasmagoric or imaginary. (ÉP)